Enterobacterial type three secretion system effectors and their interference with host innate immunity - Wu, Miaomiao (Kansas State University, 2019)
Microbial pathogens have evolved secretion systems to deliver arsenals of virulence proteins (effectors) to disrupt host homeostasis and manipulate host immune defenses. The best-characterized system mediating effector delivery into host cells is type III secretion system (T3SS) expressed by Gram-negative bacteria, including enteric pathogens enteropathogenic/enterohemorrhagic Escherichia coli (EPEC/EHEC), Shigella, Yersinia, and Salmonella. Pathogen-host cell protein interactions within the host cell alter host cell signaling and ultimately subvert pathogen-induced inflammatory response. In the first project, we identified the Salmonella Secreted Effector L (SseL) that deubiquitinated ribosomal protein S3 (RPS3) to inhibit its nuclear translocation. RPS3 guides the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) subunits to specific kB sites and plays an important role in the innate response to bacterial infection. Two E. coli effectors block RPS3 nuclear translocation. Non-locus-of-enterocyte-effacement (non-LEE) encoded effector NleH1 inhibits RPS3 phosphorylation by IKK-β, an essential aspect of the RPS3 nuclear translocation process. NleC proteolysis of p65 generates an N-terminal p65 fragment that competes for full-length p65 binding to RPS3, thus also inhibiting RPS3 nuclear translocation. Thus, E. coli has multiple mechanisms by which to block RPS3-mediated transcriptional activation. With this in mind, we considered whether other enteric pathogens also encode T3SS effectors that impact this important host regulatory pathway. In this study, we report that SseL, which was previously shown to function as a deubiquitinase and inhibit NF-kB signaling, also inhibits RPS3 nuclear translocation by deubiquitinating this important host transcriptional co-factor. RPS3 deubiquitination by SseL was restricted to K63-linkages and mutating the active-site cysteine of SseL abolished its ability to deubiquitinate and subsequently inhibit RPS3 nuclear translocation. Thus, Salmonella also encodes at least one T3SS effector that impacts RPS3 activities in the host nucleus. In the second project, we attempted to identify a cofactor involved in the interaction between E. coli effector NleH1 and host kinase the IkB kinase-β (IKKβ). The EHEC NleH1 effector inhibits NF-kB pathway by reducing the nuclear translocation of RPS3. NleH1 prevents RPS3 phosphorylation by IKKβ. IKKβ is a central kinase in the NF-kB signaling pathway, yet the EHEC NleH1 effector only restricts the phosphorylation of a subset of the IKKβ substrates. We hypothesized that a protein cofactor might dictate the inhibitory specificity of NleH1 on IKKβ. We used mass spectrometry and determined that heat shock protein 90 (Hsp90) interacts with both NleH1 and IKKβ, and that inhibiting Hsp90 activity reduces RPS3 nuclear translocation. In the third project, we focused on the crystal structures of Salmonella secreted effector SseK1 and SseK2 from Salmonella typhimurium SL1344, and non-LEE encoded effector NleB2 from E. coli O145:H28 and propose catalytic residues for arginine glycosylation. Salmonella SseK1 and SseK2 are E. coli NleB1 orthologs that behave as NleB1-like glycosyltransferases, although they differ in protein substrate specificity. The bacterial effectors SseK and NleB1 glycosylate host cell death domain target proteins on arginine residues that inhibits death receptor signaling. We report crystal structures of SseK1, SseK2, and NleB2 and found they are highly similar to each other and comprises three domains including helix-loop-helix (HLH), lid, and catalytic domain. His-Glu-Asn (HEN) motif in the active site is essential for enzyme catalysis. We observe differences between SseK1 and SseK2 in interactions with substrates and identify substrate residues that are important for enzyme recognition.
Keywords: Pathogen; Type three secretion system; Effector; NF-kB; RPS3; SseL; Hsp90